Frying performance of palm-based solid frying shortening - Omar, Muhammad Nor; Muhd Nor, Nor Nazuha; Muhd Nor, Nor Dalilah; Mat Sahri, Miskandar (Asian Network for Scientific Information, 2010)
In order to evaluate the frying performance of palm-based solid frying shortening against standard olein, the fresh potato chips were fried in both frying media using an open fryer. After frying the chips for 40 h in an open batch fryer, it was found that the frying quality of palm-based solid frying shortening was better than standard palm olein in terms of Free Fatty Acid (FFA) values, Total Polar Content (TPC) and Total Polymeric Material (TPM). Solid shortening gave FFA, TPC and TPM values of 0.7, 15.3 and 2.67%, respectively, whilst standard palm olein gave values for FFA, TPC and TPM of 1.2, 19.6 and 3.10%, respectively. In terms of sensory mean scores, sensory panelists preferred the color of potato chips fried in solid shortening on the first day of frying, while on the third and fifth day of frying there were no significant differences (p < 0.05) in the sensory scores of fried products in both frying mediums. However, on the fifth day of frying, panelists gave higher scores in terms of taste, flavor and crispness for potato chips fried in solid shortening. These findings show that the palm-based solid shortening is better than palm olein when used for deep fat frying in terms of FFA values, total polar content and total polymeric material, especially for starch-based products such as potato chips. The result also shows that, in terms of sensory mean scores, after frying for 40 h, the sensory panelists gave higher scores in terms of taste, flavor and crispiness for potato chips fried in palm-based solid shortening.